No place like home: assessing the multidimensional habitat use of endangered Arabian Sea humpback whales (Megaptera novaeangliae, Borowski 1781) with satellite telemetry - Andrew John Willson; Robert Baldwin; Simon Childerhouse; Salvatore Cerchio; Tim Collins; Tilen Genov; Ygor Geyer; Howard Gray; Brendan John Godley; Suaad Al Harthi; Aida al Jabri; Amy Kennedy; et al. (Frontiers in Marine Science, 2026)
The Arabian Sea humpback whale ( Megaptera novaeangliae ; ASHW) is understood to be the only population of this species that does not undertake long-range seasonal migrations between high- and low-latitude waters. Until recently, understanding the movements and range of individual ASHWs has relied mainly on comparisons of dorsal fin and tail-fluke images archived in photo-identification catalogues and on observations made during small-vessel surveys off the coast of Oman since 2000. The ASHW population is classified as Endangered by the IUCN Red List of Threatened Species, with an estimated 82 individuals off Oman’s coast (95% CI: 60–111), and faces increasing anthropogenic threats throughout its known range. To better understand the spatial ecology of this population, 14 Argos-enabled satellite tags were attached to ASHW off the Arabian Sea coast of Oman between February 2014 and December 2017. Individuals were tracked for a total of 749 days (mean=53, SD = 42, range=18–163 days) producing 484 days of depth-use data (mean=44, SD = 26, range=15-87). Home ranges extended along the western Arabian Sea coastline of northern Yemen and southern Oman, with a core area in the Gulf of Masirah (Oman). Switching state-space models revealed predominant area restricted search behavior (associated with breeding and foraging behavior) over continental shelf areas, with transiting movements occurring further offshore. The widest-ranging individual (a female, tag longevity 120 days) completed a round trip across the Northwest Indian Ocean between the Gulf of Masirah and the Gulf of Mannar (India). The track of this animal, and others along the coast of Oman, revealed an overlapping relationship between ecological drivers related to habitat use, including foraging and breeding, with fishing and shipping activities. The findings demonstrate the unique ecology of ASHW compared to other humpback whale populations and underscores the need for national and international authorities to incorporate these results into management initiatives to safeguard this small and Endangered population.

Urban wash-off of tire wear particles - Hannah Hapich; Tim H.M. van Emmerik; Kryss Waldschläger; Benjamin Maurer; Zhaoqing Yang; Andrew B. Gray (Journal of Hydrology, 2026)

Globalism, localism and blue food systems – How can cross-scale tensions be reduced? A production perspective from UK seafood stakeholders - Alex J. Caveen; Bryce D. Stewart; Cameron Moffat; Daniel Skerritt; Estelle Jones; Huw Thomas; Lara Funk; Magnus Johnson; Mike Cohen; Michael Roach; Neil A. Auchterlonie; Samuel Peacock; et al. (Marine Policy, 2025)

Recognising and Protecting the National Benefit of Sustainable Fisheries in the UK - Sarah Coulthard; Ainsley Hatt; Phoebe Lewis; Bryce D. Stewart; Michael Roach; Robert Clark; Sam Fanshawe; Carole Sandrine White; Julie Urquhart; Jerry Percy; Tim Gray; Emily Bulled; et al. (Fish and Fisheries, 2025)
Sustainable commercial fishing makes valuable contributions to coastal regions and broader national benefits. This paper offers three arguments in relation to what is required for the societal benefits of sustainable fisheries to be fully realised and considers each in the context of the UK but with global relevance. First, there is a need to raise the profile of the full range of benefits that are delivered through sustainable fisheries to coastal communities and the broader public. In the UK, the delivery of a ‘national benefit’ objective through fisheries is now enshrined in law by the Fisheries Act, 2020; we operationalise this through a new framing that distils eight ‘national benefits’ that all sustainable fisheries should deliver. Second, better acknowledgement of what society gains from sustainable fisheries must be paralleled with recognition of what society is simultaneously at risk of losing through the decline of the fishing fleet. We detail this decline in a new analysis of long‐term UK data, which highlights that the decline is unequally felt, with some regions of the UK, and small‐scale fishing sectors, experiencing loss more acutely. This reality leads us to argue a third point, that if society is to retain and truly harness the benefits that flow from sustainable fisheries, governing bodies must act quickly to ensure that fisheries are environmentally sustainable, diverse and inclusive, pursuing fisheries that ‘leave no one behind’.

Unregulated Open-Access versus Regulated Open-Access Fishing: Stakeholders Perceptions in Sierra Leone - Nwamaka Okeke-Ogbuafor; Tim Gray (Fishes, 2024)
Fish stocks are declining in marine capture coastal fisheries in West Africa. Many observers have blamed climate change and the system of open access for the decline. Open-access fishing encourages too many people to take up fishing, and the result is overfishing of the stocks. According to such critics, this is a classic example of Hardin’s tragedy of the commons, whereby a continuous increase in the number of users of a natural resource eventually leads to the collapse of the resource. The present study, which analysed stakeholders’ perceptions about their open-access fishing in Siera Leone’s marine fisheries, conducted 32 key informant interviews. Our research found that while they perceived that open-access fishing impacted fish stocks, most Sierra Leone’s marine capture fishers did not see open access as a cause of fish decline; instead, they blamed the lack of enforced regulations on the methods and extent of fishing. Accordingly, these fishers favoured the continuation of open access—not least because it helps to alleviate hunger and is a readily available source of protein in Sierra Leone’s coastal communities—but accompanied by strict regulations on both the type of fishing gear used and the quantity, size, and species of fish caught. In other words, they preferred regulated open access to unregulated open access. The central government’s resolve to regulate its fishery will determine whether it will transition from unregulated open access to regulated open access or other forms of OA. This study recommends detailed research into how to influence political will to enforce regulations.

Fishing Europe’s Troubled Waters: 50 years of Fisheries Policy,Fishing Europe’s Troubled Waters: 50 years of Fisheries Policy, by David Symes, Routledge, 2023; paperback £29.99; www.routledge.com/9781032424705 - Tim Gray (Reviews in Fisheries Science & Aquaculture, 2024)

Climate-smart fisheries: CO2 emissions reduction and food security are complementary - Nwamaka Okeke-Ogbuafor; Tim Gray; Sheku Kamara; Edward Sesay; Abdulai Dauda; Selina M Stead; Danielle Robinson; Kelechi Johnmary Ani (Marine Policy, 2024)

An evaluation of Oman’s National Fisheries Development Strategy (NFDS) 2013–2020: Wealth or welfare maximisation? - Khalid Al-Subhi; Tim Gray; Selina M. Stead (Marine Policy, 2023)

Proposed Solutions to the Problems of the Lake Chad Fisheries: Resilience Lessons for Africa? - Nwamaka Okeke-Ogbuafor; Tim Gray; Kelechi Ani; Selina Stead (Fishes, 2023)
Fishing communities in Lake Chad are experiencing humanitarian crises—more than five million people in the region are hungry and malnourished—and fishers are in dire need of improved fisheries management policies. Understanding the fishers’ resilience, and how they perceive their fisheries policies, could provide an opportunity for governments and fisheries managers to refine their policies. The present study, which is based on 38 semi-structured interviews carried out between January and April 2022 on the Nigerian shores of Lake Chad, breaks new ground, firstly by seeking to understand the issues raised by declining fish stocks in Lake Chad from the viewpoints of fishers themselves; and secondly by making use of resilience theory to interpret the fishers’ responses to their situation. Our findings are that the fishers have a surer grasp of the most effective resilience strategies available to them than external bodies; and that the fishers’ adaptive resilience and local knowledge provide a framework for developing smarter fisheries management policies for Lake Chad. This study provides evidence to support recommendations for Africa’s supranational, national and local governments to invest in, and make use of, the fisheries research on the ground to address the problems facing its fisheries, rather than experimenting with seemingly random ideas from across the globe. The Lake Chad fisheries crisis is an extreme case demonstrating the harmful effects of external influences from which the fisheries of other African countries can learn lessons.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Comparative biogeography and the evolution of population structure for bottlenose and common dolphins in the Indian Ocean - Howard W. I. Gray; Ing Chen; André E. Moura; Ada Natoli; Shin Nishida; Shinsuke Tanabe; Gianna Minton; Louisa S. Ponnampalam; Muhammad S. Kiani; Ross Culloch; Mauvis Gore; Anna Särnblad; et al. (Journal of Biogeography, 2021)
Aim In the marine environment, where there are few physical boundaries to gene flow, there is often nevertheless intraspecific diversity with consequences for effective conservation and management. Here, we compare two closely related dolphin species with a shared distribution in the Indian Ocean (IO) to better understand the biogeographic drivers of their population structure. Location Global oceans and seas with a focus on the Indian Ocean Taxon Tursiops sp. and Delphinus sp. Methods Bayesian, ordination, assignment, statistical and phylogenetic analyses to assess phylogeography, connectivity and population structure using microsatellite and mitochondrial DNA genetic markers. Results Both Tursiops sp. and Delphinus sp. showed population structure across the western IO and, in each case, populations in the Arabian Sea (off India, Pakistan and Oman) were most differentiated. Comparisons with other populations worldwide revealed independent lineages in this geographic region for both genera. For T . aduncus , (for which multiple sites within the IO could be compared), Bayesian modelling best supported a scenario of expansion southwards following a bottleneck event resulting in differentiation between the northern and western IO. For Delphinus, the same pattern is even more pronounced. Populations in the Arabian Sea region of the north‐western IO show genetic isolation for each of the two genera, consistent with other studies of cetacean species in this region. Main conclusions We propose that changes in the intensity of the southwest monsoon during the climate cycles of the Pleistocene could have affected regional patterns of productivity and represent an important biogeographic driver promoting the observed patterns of differentiation and population dynamics seen in our focal species. Patterns of population genetic structure are consistent with phenotypic differences, suggesting an influence from distinct habitats and resources, and emphasising the need for effective conservation measures in this geographic region.

A value chain analysis of Malaysia’s seaweed industry - Adibi M. Nor; Tim S. Gray; Gary S. Caldwell; Selina M. Stead (Journal of Applied Phycology, 2020)
A global shortfall in protein supply from capture fisheries has motivated the Malaysian government to revise its aquaculture strategy, focusing on three commodities: seaweed, fish and marine shrimp. However, the performance of the Malaysian aquaculture sector, particularly seaweed production, is poorly documented. This is the first empirical study to undertake a value chain analysis (VCA) of the Malaysian seaweed sector using stakeholder perceptions and secondary data that encompass members of seaweed farming cooperatives (the Semporna Area Farmers’ Association and the governments’ flagship Seaweed Cluster Project). Fieldwork was conducted between April and June 2015 among seaweed stakeholders involved in the value chain using a mixed methods approach—in-depth interviews with key informants, focus group discussions, household surveys, personal observation and secondary data. Qualitative and quantitative data were collected from both upstream (seaweed farming, marketing structure and the Malaysian Good Aquaculture Practices [MyGAP] certification programme) and downstream (seaweed processing) activities involving farmers, intermediaries/middlemen (buyers), processors and officials. Kappaphycus spp. was sold in two forms: (1) dried seaweed to be used as raw materials in carrageenan processing (approximately 90% of total harvest) and (2) fresh seaweed to be used as a source of seedlings (approximately 10% of total harvest). The value chain ended with the carrageenan form, which is exported to international markets. The price of dried seaweed varied according to a combination of seaweed quality, the strength of farmer’s relationships with intermediaries and processors and in response to demand from the carrageenan industry. The prices obtained by Malaysian farmers for dried seaweed and carrageenan remained low, US$ 0.60 and US$ 4.43 per kg, respectively, despite efforts by the government to enhance the value chain by imposing seaweed standards (via MyGAP) for farm management, dried seaweed and semi-refined carrageenan. The VCA was a useful tool to identify and map the market, with the results providing a better understanding of the seaweed sector, which could be helpful in supporting further aquaculture development in Malaysia.

Improving bycatch mitigation measures for marine megafauna in Zanzibar, Tanzania - Yussuf N. Salmin; Narriman S. Jiddawi; Tim Gray; Andrew J. Temple; Selina M. Stead (Western Indian Ocean Journal of Marine Science, 2019)

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

Perceptions of Threats Facing Cabo de Palos - Islas Hormigas MPA and Potential Solutions - Katie Hogg; María Semitiel-García; Pedro Noguera-Méndez; Tim Gray; Sarah Young (Coastal Management, 2018)

Is a cooperative approach to seaweed farming effectual? An analysis of the seaweed cluster project (SCP), Malaysia - Adibi M. Nor; Tim S. Gray; Gary S. Caldwell; Selina M. Stead (Journal of Applied Phycology, 2017)

Characterisation of 9 polymorphic microsatellite markers for the Critically Endangered lemur leaf frog Agalychnis lemur - Alex Petchey; Andrew Gray; Claes Andrén; Tim Skelton; Brian Kubicki; Calvin Allen; Robert Jehle (Conservation Genetics Resources, 2014)

Environmental justice of nuclear waste policy in Taiwan: Taipower, government, and local community - Gillan Chi-Lun Huang; Tim Gray; Derek Bell (Environment, Development and Sustainability, 2013)

Carbon Cycling in Floodplain Ecosystems: Out-Gassing and Photosynthesis Transmit Soil δ13C Gradient Through Stream Food Webs - Duncan P. Gray; Jon S. Harding; Bo Elberling; Travis Horton; Tim J. Clough; Mike J. Winterbourn (Ecosystems, 2011)

Urinary creatine profiles after administration of cell-specific testicular toxicants to the rat - Nigel P. Moore; Dianne M. Creasy; Tim J. B. Gray; John A. Timbrell (Archives of Toxicology, 1992)